Travel Demand Management Policy Instruments, Urban Spatial Characteristics, and Household Greenhouse Gas Emissions from Travel in the US Urban Areas - Su, Qing (International Journal of Energy Economics and Policy, 2017)
This paper examines the impact of travel demand management policy instruments and a wide variety of measures of urban spatial characteristics on CO2 emissions from household travel based on more than 27,000 observations from the 2009 NHTS. The regression results indicate that travel demand management (TDM) instruments and urban spatial characteristics affect CO2 emissions from household travel in a complicated way. Population-weighted density, rail availability, and TDM instruments such as parking management, promotion of transit use and carpool, and employer-based TDM programs have a moderate but negative impact on CO2 emissions from household travel. On the other hand, employment and population distribution imbalance and major road network density have a moderate but positive impact on CO2 emissions from household travel. Keywords: parking management; promotion of transit use and carpool, employer-based TDM program; CO2 emissions from household travel; population-weighted density; employment and population distribution imbalance JEL Classifications: Q2, Q5